Educational Robotics Teaching with Arduino and 3D Print Based on Stem Projects - Souza, Tiago; Elisiario, Larissa (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This paper aims to explore the possibility and the experience in educational robotics classes with Arduino and 3D prints for children and teenagers aged 10 to 17 years old. It presents how these two tools can be very useful together to teach basic concepts of Science, Technology, Engineering and Math (STEM). The main focus is to describe how some projects were selected by students, how they built them, what kind of challenges were found and what possibilities of learning and teaching there were in this context.